Load-bearing aerobic exercise prior to injury moderates systemic immunosuppression response to fracture - Strait, Lia K.; Dewan, Dayne; Williams, Kylie E.; Guyer, Tyler; Willett, Nick J.; Guldberg, Robert E. (Frontiers in Physiology, 2025)
Bone fracture non-unions are common and often lead to costly revision surgeries, long-term patient pain and loss of function. Identifying fractures at-risk for non-union remains challenging due to an incomplete understanding of underlying mechanisms. Preclinical and clinical studies have shown that dysregulated immune responses are linked to impaired healing. These studies have also identified fracture characteristics, biologic factors, and lifestyle habits associated with a higher risk of poor healing. However, the impact of exercise history on the immune response to fracture remains underexplored. Load-bearing aerobic exercise is known to modulate properties of bone and systemic inflammation, suggesting that exercise history could influence post-fracture immune responses and healing outcomes. Using a rat treadmill exercise and femoral segmental defect model, this study sought to determine if regular exercise pre-fracture affects the systemic immune response and healing outcomes. We hypothesized that pre-fracture treadmill running would attenuate immunosuppressive mediators—shown previously to correlate with poor healing—and improve bone regeneration compared to sedentary controls. Subjects that exercised before fracture had decreased post-fracture circulating immunosuppressive myeloid-derived suppressor cells and pain sensitivity, however there was no significant effect of prehabilitation on bone repair volume, defect bridging rate, or biomechanical properties.